Turkey : Report on Observance of Standards and Codes-Fiscal Transparency Module-Update. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This paper discusses the first Report on Observance of Standards and Codes (ROSC) for Italy. IMF staff reviewed developments in Italy's observance of fiscal transparency practices, with a view to updating changes in current practices, reviewing progress in implementing the initial ROSC's recommendations, and identifying developments relevant for future observance of good fiscal transparency practices.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet